Edukasi dan Pendampingan Ibu Bersalin Kala 1 dalam Melakukan Mobilisasi di Ruang Bersalin Puskesmas Paiton - Yusri Dwi Lestari; Siti Jiyadatun Nafi'ah; Putri Novia Pramudita (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Childbirth is the birth of the baby, placenta and amniotic membranes from the uterus to the outside world. Long labor causes mothers to experience stress and fatigue for longer so that pain will increase. The causes of labor pain are caused by various factors such as uterine muscle contractions, stretching of the pelvic floor muscles, episotomy and psychological conditions, namely anxiety which can increase the incidence of stress. To overcome prolonged labor, active labor techniques have been introduced. The active labor method has actually been implemented as one of the care services during the birth process, namely in terms of mobilization which encourages the mother to choose the position that is considered the most comfortable with the aim of minimizing pain and which can affect the length of labor. labor. first and second stages of labor. In reality, there are still many mothers who give birth who experience difficulty in mobilizing and positioning and only focus on the pain and are afraid to move so they only stay in one position during the birth process, this can make the muscles stiff and cause pain. it is difficult for the fetus to descend into the pelvis. Based on research, pregnant women who carry out mobilizations such as walking lightly and arranging a comfortable position can speed up the descent of the head and the opening of the cervix. This service takes the form of providing education about the benefits of mobilization for mothers during the first stage of labor and providing assistance with mobilization in the delivery room. Providing education and assistance can help mothers in labor empower themselves in undergoing labor so that it is hoped that labor can run smoothly. This community service can help mothers in labor to empower themselves to mobilize in an effort to speed up the descent of the fetal head, speed up opening and the mother can adjust to a comfortable position so that the birth runs smoothly.